The effects of direct and indirect training in metacognitive learning strategies on near and far transfer in self-regulated learning. (February 2023) - Schuster, Corinna; Stebner, Ferdinand; Geukes, Sebastian; Jansen, Malte; Leutner, Detlev; Wirth, Joachim
Highlights: Strategy training has a positive effect on transfer of metacognitive strategies. Combining direct and indirect training did not reveal any differences. Only a minority of students applied metacognitive strategies. We conducted a cluster randomized control field study with a large sample. A first step toward finding ways to promote transfer in self-regulated learning.